Kahoot Ethnomatematics: Innovative Interactive Quiz Media in Spatial Geometry Learning for Ninth Grade Students - Agus Suprianto; Hidayu Sulisti (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to develop an interactive Kahoot-based quiz tool that integrates ethnomathematics into the teaching of three-dimensional shapes. The background of this study is students’ difficulty in understanding concepts and formulas, as well as the limited use of technology-based learning tools that highlight local wisdom. The method used is Research and Development (R&D) with a 4-D development model modified into a 3-D model (Define, Design, Develop). The study subjects included 4 mathematics lecturers and 3 junior high school teachers at the Assalam Islamic Boarding School in Pontianak. Data collection techniques used interviews and questionnaires, while validation analysis was conducted using Gregory’s theory. Results from the define stage indicated a high need for innovative and enjoyable learning. In the design phase, the media was organized through a storyboard and then validated in the development phase. The analysis results showed a Content Validity Index (CVI) of 0.93 for the media aspect and 1.00 for the language and content aspects, which fall into the very high validity category. Thus, this interactive quiz media is deemed suitable for use in supporting competitive, meaningful, and contextual learning through the integration of culture and technology. However, this study is limited to the development phase and does not include a large-scale pilot test; furthermore, it has not measured the impact on student learning outcomes. Therefore, it is recommended that future research conduct a more extensive field trial and assess the effectiveness of the media on student learning outcomes, motivation, and engagement